On Maps of Period 2 on Prime and Semiprime Rings - H. E. Bell; M. N. Daif (International Journal of Mathematics and Mathematical Sciences)
A map f of the ring R into itself is of period 2 if f2x=x for all x∈R; involutions are much studied examples. We present some commutativity results for semiprime and prime rings with involution, and we study the existence of derivations and generalized derivations of period 2 on prime and semiprime rings.